Distributions and Physical Properties of Molecular Clouds in the G24 Region of the Milky Way - Tian Yang; Xi Chen; Xiao-Yun Xu; Yang Yang; En Chen; Jun Li; Bing-Gang Ju; Deng-Rong Lu (The Astronomical Journal)
We report the spatial distribution and physical characteristics of molecular clouds in the G24 region, which is located near the intersection of the Milky Way’s Galactic bar with the Norma arm and the 3 kpc arm. Utilizing molecular line data from the Milky Way Imaging Scroll Painting project, including ^12 CO, ^13 CO and C ^18 O, along with our own observations of the HCO ^+ line using the Purple Mountain Observatory 13.7 m telescope, we reveal the complex architecture of molecular clouds in the G24 region. Seven giant molecular clouds, each with a mass exceeding 10 ^4 M _⊙ and a typical H _2 column density of 10 ^21 cm ^−2 , have been identified through observations of CO and its isotopes. The conversion factor X _CO for the G24 region is estimated to be 8.25 × 10 ^19 cm ^−2 (K km s ^−1 ) ^−1 , aligning with the typical values observed in other regions. Adopting the GaussClumps algorithm, we identify a total of 257, 201, and 110 clumps in ^12 CO, ^13 CO and C ^18 O within the G24 region, respectively. The derived physical properties (including effective radius, mass, and virial parameter) indicate that the majority of these clumps are gravitationally bound, with a subset possessing the potential to form massive stars. Examination of gas infall activities within these clumps further suggests ongoing massive star formation. The complex physical and kinematic environment, shaped by the G24 region’s unique location within the Milky Way, has limited the clear detection of gas outflows.